HUBUNGAN KEMAMPUAN KONEKSI DAN KEMANDIRIAN BELAJAR SISWA - firliani; nurhikmayati, iik (Papanda Publisher, 2022)
This study examines the relationship between the ability to connect mathematically independent learning. Mathematical connection ability is closely related to real life. Learning activities that connect lessons with daily life will also be able to increase learning independence in students. Independence in learning can be interpreted as active learning activities on the basis of their own volition or appearing within themselves without being required and directed. This research is a study of a number of literatures. The literature review that supports the theoretical analysis approach includes: learning theories, connection abilities and learning independence. The sources of this research study are reference books, scientific journals and other supporting media. The results of the study are, students' connection abilities will be formed by the formation of good student learning independence. The better the learning independence, the easier it is for students to develop their mathematical connection abilities.